Retinal Manifestations of Hypertensive Disorders in Pregnant Women: Insights from a Rural Antenatal Cohort - Dr Sanjana Reddy; Dr Shivani Namala; Dr Rupanjali J; Dr Narayan Hod, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pregnancy-Induced Hypertension (PIH) poses serious risks to maternal and foetal health. This cross-sectional study evaluated retinal changes in 103 hypertensive pregnant women in a rural tertiary care setting. Fundus abnormalities were found in 37.9% of cases, with AV crossing changes and Grade 2 hypertensive retinopathy being most common. Significant associations were observed with blood pressure, gestational age, visual acuity, and occupational status. Fundoscopic screening can aid in early detection and management of systemic hypertension during pregnancy Background: Pregnancy-Induced Hypertension (PIH) is a prevalent complication during pregnancy, contributing significantly to maternal and foetal morbidity and mortality. Ocular changes, particularly fundus findings, can serve as early indicators of systemic vascular compromise. Introduction: This study explores the retinal manifestations of hypertensive disorders in pregnant women, with a focus on a rural antenatal cohort. Pregnancy-Induced Hypertension (PIH), including preeclampsia and eclampsia, remains a major contributor to maternal and fetal morbidity. Given the accessibility and non-invasive nature of fundus examination, this study evaluated ocular changes in 103 antenatal women with hypertension at PES Hospital using direct and indirect ophthalmoscopy. Fundus abnormalities were observed in 37.9% of cases, with AV crossing changes and Grade 2 hypertensive retinopathy being most common. Statistically significant associations were found between retinal findings and factors such as blood pressure, gestational age, gravida status, visual acuity, and occupation. The results emphasize the importance of integrating routine retinal screening into antenatal care, especially in resource-limited rural settings, to facilitate early detection and intervention for systemic hypertension and improve pregnancy outcomes. Aim: To study the fundus changes in various hypertensive disorders during the antenatal period in a rural population. Methods: A cross-sectional study was conducted on 103 antenatal women with hypertension at PES Hospital. Participants underwent visual acuity testing and fundus evaluation using direct and indirect ophthalmoscopy. Demographic, clinical, and fundoscopic data were collected and analysed using SPSS software. Results: Fundus changes were present in 37.9% of participants. The most common abnormalities were AV crossing changes (23.3%), AV narrowing (6.8%), retinal hemorrhages (4.9%), and papilledema (2.9%). Grade 2 hypertensive retinopathy was the most frequent (61.5%). Significant associations were found between fundus changes and blood pressure levels, visual acuity, gestational age, and occupational status (p<0.05). Conclusion: Fundoscopic examination is a non-invasive, cost-effective tool that provides valuable insight into the systemic impact of hypertension in pregnancy. Routine retinal screening in antenatal care—especially in rural settings—can aid in early detection, timely intervention, and improved maternal and fetal outcomes.